互嵌性秩序博弈: 基层社会冲突根源及其阻力探微——基于反向秩序的视角. - 胡锐军 (Journal of Xi'an Jiaotong University (Social Sciences), 2025)
Social conflict is the key source and key code that determines social change and explains social movements. As a cornerstone of social stability, the level of social conflict management in counties plays an indispensable role in maintaining grassroots stability. Due to the close relationship between order and conflict, exploring social conflict governance issues from the perspective of order has always been an important research direction for scholars. forming different technical or logical paths. Conflict theory, together with functional theory and interactionism, constitutes the three major theoretical paradigms for analyzing the evolution of social order. However, most of these scholars consider order construction and social conflict governance issues from the perspective of positive order description. From the perspective of reverse order in genetics, the interactive characteristics of the evolution of social conflicts and changes in social order determine that the process of modernizing grassroots governance is a process of competition and replacement between old and new orders. The smoothness and stability of order changes directly determine the degree of risk. Analyzing the triggering roots and manifestations of social conflicts from the perspective of reverse order has become a possible and new path. This article takes the theory of reverse order as the analytical framework, and explores in depth the root causes and resistance manifestations of the interlocking order of grassroots social conflicts from the perspective of reverse order. Through normative exploration and empirical analysis, it is found that in the process of modernity, as China is in the sprint stage of advancing Chinese path to modernization, the change of governance order is constantly going through the competition, mutual exclusion and confrontation between the new and old orders. The new and old orders are mixed and replaced in the mutual exclusion, mutual fusion and interaction relationship of breaking the establishment. preservation and abolition. reflecting a very obvious embedded game form, which is mainly reflected in the interaction of six pairs of antithetical orders, namely: construction order and spontaneous order, rural order and urban order, difference order and equal order. rule of etiquette order and rule of law order, closed order and open order, inward rank order and outward order. It is precisely these new and old orders that are mutually embedded and mutually exclusive. The battle of style, tangible and intangible, constitutes an important source of resistance to the change of modern order and social conflict risk, because its game results will automatically project and reflect onto social risk sources, and manifest in different forms of resistance. Compared with previous research, the contribution of this article mainly lies in two aspects: firstly, it constructs a theoretical analysis framework of the reverse order perspective and the logical framework of the interaction and resistance extension between the positive and negative orders. further confirming that the trajectory of the change of social governance order in counties must be oscillating or even swinging and advancing: Secondly, specific forms of opposition between positive and negative orders were selected from the concrete forms of the ideal social order, and corresponding analyses were conducted on their resistance manifestations, revealing the root causes of social conflicts in counties, namely the resistance encountered or newly emerged in the process of the interweaving and interaction. between old and new orders, which includes both the natural obstacles of traditional order and the drawbacks of modern order itself, as well as new problems formed in the game between the two. This study breaks away from the traditional paradigm of social conflict research and conducts a detailed analysis of the root causes and resistance forms of county-level social conflicts from the perspective of reverse order. The ecological political model is a model that breaks through the game resistance and breaks through the constraints of existing circles and misconceptions in grassroots social conflict governance.